Fikih Lingkungan: Revitalisasi Pengelolaan Sampah di Kota Kendari - Andi Yaqub; Fatihani Baso; Eka Sufartianinsih Jafar; Iswandi Iswandi (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2022)
This study aims to provide a database of waste distribution patterns and describe paradigm variants in waste processing in Kendari City and hack acceptance of environmental jurisprudence as a theological approach in the practical practice of waste control. Root cause identification and precision analysis in the form of management area surveys, observation and sorting of waste materials, in-depth interviews, and aerial photographs (UAVs). The results showed that the pattern of waste distribution in Kendari City was measured through education level, income level, number of members in the KK, and type of work affecting the large volume of waste disposal and waste dominated by food waste and waste.  Consumptive behavior describes a practical and pragmatic perspective seen in the behavior of people who use disposable materials and dispose of garbage instead of in landfills, which results in many wastes generation points. The Muslim community of Kendari City has not fully understood and realized the consequences of Islamic law related to environmental pollution. The review of environmental jurisprudence is expressly in the provisions of the law that it is mandatory to preserve the environment and that it is legally illegal to dispose of garbage in any place. Optimization can be reaped by actively implementing the Kendari City government as a service provider by preparing infrastructure for organik and inorganic waste management and providing counseling on the benefits of waste management. The participation of the community begins with understanding and theological awareness related to aspects of behavior, operational techniques, and environmental sustainability by practicing the 5R's towards Kendari City Zero Waste Home.